Assessing sustainability of smallholder dairy and traditional cattle milk production systems in Tanzania - Munyaneza, C. (Sokoine University of Agriculture, 2018)
Sustainability of smallholder dairy and traditional cattle milk production systems in developing countries, including Tanzania, is limited by a number of constraints such as low cow productivity, shortage of feed, limited access to inputs and outputs markets and degradation of natural resources. Efforts have been made to improve the sustainability, but the improvement is hindered by lack of knowledge on how to ensure sustainability of the production systems particularly at the farm level. To contribute to the efforts being made to address these issues, this study aimed at assessing sustainability of smallholder dairy and traditional cattle milk production systems in Tanzania. The study was conducted in four districts located in Morogoro and Tanga Regions. In the context of this study, a smallholder dairy production system refers to a system with dairy farms which have up to five dairy cows, where majority are crossbreeds of local and pure exotic breeds and milk is considered the main source of income. Meanwhile, a traditional cattle milk production system consists of cattle farms keeping mainly indigenous cattle and milk is not considered the main source of income.